Electrocatalytic synthesis of heterocycles from biomass-derived furfuryl alcohols - Xuan Liu (Nature Portfolio, 2021)
The synthesis of heterocyclic moieties pertaining to biologically active molecules from biomass-based starting compounds is very attractive yet underexplored. Herein, the authors report an electrocatalytic Achmatowicz reaction for the synthesis of hydropyranones from biomass-derived furfuryl alcohols.